Traditional Ecological Knowledge (TEK) Masyarakat Adat dalam Pengelolaan Lingkungan di Kabupaten Landak - Sesario, Revi; Th. Candra Wasis Agung Sutignya; Janne Hillary (Vokasi: Jurnal Publikasi Ilmiah, 2024)
Indigenous peoples, especially the Dayak Kanayant tribe in West Kalimantan, play a key ecological role in protecting the environment for generations through local wisdom. The position of the community is sometimes marginalized and marginalized and even conflicts with oil palm plantation companies cannot be avoided. Many reports show that sometimes customary land rights are grabbed, resulting in agrarian conflicts that lead to violations that require legal action by the police and courts. Applied research entitled “Traditional Ecological Knowledge (TEK) of Indigenous Peoples in Environmental Management in Landak Regency”. This research aims: to find out the local wisdom of Dayak indigenous peoples in managing the environment through TEK to support environmental sustainability in overcoming climate change and deforestation issues that occur in West Kalimantan. A survey research method with a case study model was used to achieve the research objectives. Data collection used the Focus Group Discussion (FGD) method, in-depth interviews, observation and documentation. The results revealed that Dayak indigenous people have awareness and motivation in forest and environmental conservation activities in the norms and customary rules that apply in Landak Regency. Customary Forests are still considered sacred to the Dayak community so that they are highly preserved, the majority of people work by farming and planting. The traditional agricultural ceremony (bahuma) carried out by the Dayak Kanayan Community in Saham and Paloan Villages is a process from the initial farming activities to the activities of harvesting rice with wisdom and cultural heritage. Advice in this research is that there is a need for a regional regulation on the determination of sustainable agricultural land and an effort to protect the rights of indigenous peoples and customary land from the Regional Government of Landak Regency.